Análisis jurídico de la inestabilidad laboral del servidor público con nombramiento provisional que ha sido declarado ganador del concurso de méritos y oposición - Duran Vega, David José (2015)
The legal issues concerning this investigation is aimed at legal analysis of the legal framework on labor in Ecuador is crucial for its significance in the legal relations arising from the contractual relationship between the public servant and public administration in any institutional forms, being then postponed the treatment of issues inherent in the legal treatment to be an official. However it is necessary to identify the extent to which is guaranteeing the right to work and all the prerogatives of the public servant as both worker and labor principles according to our Constitution must be observed optimally without restriction of any kind. It is worth mentioning that the Organic Law of the Public Service as a relatively new law in the country, has brought remarkable changes in the contractual regulation with the public server, setting new figures within the public sector. In accordance with the available literal quoted above, we can see that the General Regulation of the Organic Law of Public Service also refers to this figure of provisional appointments in the following terms: "B) Provisional: Those granted to temporarily fill the positions identified in paragraph b) of Article 17 of the LOSEP; will not generate stability right or server; " With this background, it appears that the server has been postulated on merit and opposition to enter the civil service and has won, even when they had been extended his appointment, he has the character of provisional, that is to elapse probation for a period of three months, leading to a climate of legal uncertainty, employment instability to the official in question, but having won the competition, no insurance entry into the career of public service, it must demonstrate during three months their skills, knowledge, skills and abilities, which logically means and has shown during the process of evaluation and assessment of their merits and knowledge in the contest